Pregnancy after loss during the COVID19 pandemic - Pollock, Danielle (Women Birth, 2020)
BACKGROUND: Rapid changes to how maternity health care is delivered has occurred in many countries across the globe in response to the COVID-19 pandemic. Maternity care provisions have been challenged attempting to balance the needs and safety of pregnant women and their care providers. Women experiencing a pregnancy after loss (PAL) during these times face particularly difficult circumstances. AIM: In this paper we highlight the situation in three high income countries (Australia, Ireland and USA) and point to the need to remember the unique and challenging circumstances of these PAL families. We suggest new practices may be deviating from established evidence-based guidelines and outline the potential ramifications of these changes. FINDINGS: Recommendations for health care providers are suggested to bridge the gap between the necessary safety requirements due to the pandemic, the role of the health care provider, and the needs of families experiencing a pregnancy after loss. DISCUSSION: Changes to practices i.e. limiting the number of antenatal appointments and access to a support person may have detrimental effects on both mother, baby, and their family. However, new guidelines in maternity care practices developed to account for the pandemic have not necessarily considered women experiencing pregnancy after loss. CONCLUSION: Bereaved mothers and their families experiencing a pregnancy after loss should continue to be supported during the COVID-19 pandemic to limit unintended consequences.